2007
DOI: 10.1210/jc.2007-0746
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Testosterone Undecanoate Every 3 Months for Testosterone Supplementation in Female-to-Male Transsexuals

Abstract: The treatment of female-to-male transsexuals with long-acting testosterone undecanoate may be a feasible and safe option for testosterone augmentation in these subjects. However, monitoring of blood pressure should not be ignored during the treatment, to identify patients liable to develop hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
93
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 37 publications
15
93
1
4
Order By: Relevance
“…However, higher-than-replacement testosterone administration has been shown to prevent hypogonadal bone loss in animal models (7,8,47) and to enhance BMD in hypogonadal elderly men (2). Likewise, testosterone administration prevents ovariectomy/hysterectomyinduced bone mineral deficits in humans (25,33,39,45,52) and animals (47) and elevates BMD in androgen-deficient females (30). In the present study, we report what appears to be the first-ever analyses of the sex hormone (i.e., testosterone, Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, higher-than-replacement testosterone administration has been shown to prevent hypogonadal bone loss in animal models (7,8,47) and to enhance BMD in hypogonadal elderly men (2). Likewise, testosterone administration prevents ovariectomy/hysterectomyinduced bone mineral deficits in humans (25,33,39,45,52) and animals (47) and elevates BMD in androgen-deficient females (30). In the present study, we report what appears to be the first-ever analyses of the sex hormone (i.e., testosterone, Fig.…”
Section: Discussionmentioning
confidence: 57%
“…At least one study has reported that slightly-higher-than-replacement testosterone administration effectively reverses BMD loss in hypogonadal elderly men (2). Moreover, several studies suggest that supraphysiogical testosterone administration to transsexuals prevents the bone loss associated with combined ovariectomy/hysterectomy and thus the near-complete ablation of gonadally derived estrogen (25,33,45,52). Overall, supraphysiological testosterone administration may be capable of preventing androgen deficiency-related bone loss; however, the sex-specific skeletal responses following testosterone administration require clarification (26,59).…”
mentioning
confidence: 99%
“…For induction and maintenance of virilization of FTM transsexuals, continuous androgen administration is necessary, both prior to sex reassignment surgery and thereafter for the remainder of the individual's lifetime to maintain virilization and, equally important, to prevent the sequelae of sex steroid deprivation (such as osteoporosis) following ovariectomy, which is part of sex reassignment surgery (2). Several reports document the use of parenteral TU in FTM (6)(7)(8). These reports indicate the feasibility and safety of the use of parenteral TU for the purpose of inducing virilization in FTM.…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone administration to FTM usually leads to no or a small decline in plasma estradiol levels (34,44). Since part of testosterone is aromatized to estradiol, plasma levels remain in such a range that biological effects can be expected (34,44).…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Since part of testosterone is aromatized to estradiol, plasma levels remain in such a range that biological effects can be expected (34,44). Consequently, testosterone treatment in FTM generates biologically active levels of estradiol (proportional to the circulating levels of testosterone and sometimes higher than in postmeopausal women receiving estrogen treatment), which are not opposed by progesterone action.…”
Section: Endometrial Cancermentioning
confidence: 99%